2022
DOI: 10.3389/fpls.2022.723356
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differentially Expressed Genes Reveal Conserved Mechanisms in the Rice-Magnaporthe oryzae Interaction

Abstract: Magnaporthe oryzae causes rice blast disease and is responsible for major losses in rice production worldwide. Although numerous studies have focused on the interactions between Oryza sativa and M. oryzae, to date, the conserved mechanisms remain in part unclear. In this study, a comparative analysis of transcriptomes of O. sativa L. ssp. japonica cv. ‘Nipponbare’ interacting with three M. oryzae strains (248, 235, and 163) were performed to explore the conserved molecular mechanisms. Differentially expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…To analyze the expression patterns of O. sativa japonica group NRP genes ( OsNRPs ) during M. oryzae infection, we calculated expression values using the data from our previously RNA sequencing (RNA-seq) [ 28 ]. In that study, O. sativa L. ssp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the expression patterns of O. sativa japonica group NRP genes ( OsNRPs ) during M. oryzae infection, we calculated expression values using the data from our previously RNA sequencing (RNA-seq) [ 28 ]. In that study, O. sativa L. ssp.…”
Section: Resultsmentioning
confidence: 99%
“…OsNRP1 was found that specifically up-regulated at an early stage during O. sativa japonica group interacting with three M. oryzae strains proposed by [ 28 ]. Inoculation assays of overexpression transgenic line ( OsNRP1 OX ) revealed that OsNRP1 slowed rice disease.…”
Section: Discussionmentioning
confidence: 99%
“…Genes with a combination of P value < 0.01 and the absolute value of |Log 2 fold change|≥ 1.5 were regarded as DEGs. For grouping DEGs with similar expression patterns, a hierarchical clustering was generated using the expression values from each library (Liang et al 2022). Analysis was conducted using Cluster 3.0 software with Pearson correlation as the distance measure.…”
Section: Identification Of Degs Of M Oryzae At Infection Stagementioning
confidence: 99%
“…Previous studies demonstrated that the infection of M. oryzae induced the expression of many host genes [17][18][19] , including transcription factor genes 20,21 . Although AP2/ERFs were known as a transcription factor family responsible for the numerous abiotic stresses in plants 22 , they were shown to play crucial roles in the regulation of biotic stress responses 4,23 .…”
Section: Design Of Sgrnasmentioning
confidence: 99%